0837 Pharmacokinetics of Sodium Oxybate in Children and Adolescents with Narcolepsy with Cataplexy. (27th April 2018) - Rosen, C L; Ruoff, C; Boyce, L H; Chen, C; Wang, Y; Parvataneni, R; Zomorodi, K; Plazzi, G
Abstract: Introduction: The efficacy, safety, and tolerability of sodium oxybate (SXB) were evaluated in a study of children and adolescents (7–17 years) with narcolepsy with cataplexy. SXB pharmacokinetics (PK) were also evaluated and further characterized using population PK (PopPK) modelling. Methods: PK sampling was performed on two nights while patients were receiving stable dose (SD) SXB, individually titrated and administered as equally divided doses (Dose 1 [D1]: ≥2 hours post-meal, Dose 2 [D2]: 4 hours post-D1). Blood sampling was performed at 0, 0.75, 1.5, 2.5, 4, 4.75, and 8 hours post-D1. D1 parameters included area under the curve (AUC0-4h ), maximum concentration (Cmax ), and time to Cmax (Tmax ); D2 parameters included C4.75h (≈Cmax ) and C8h (residual concentration). Dose proportionality (mean ratio Night 2 [full-SD]:Night 1 [half-SD]) for AUC0-4h and Cmax was also assessed. Intrinsic and extrinsic factor effects on SXB PK were evaluated by PopPK pediatric modelling built on pediatric and adult data. Results: The PK study included 29 participants (7–11 years: n=11, 12–17 years: n=18; median [range] SD: 7 g [4–9 g], 112.3 mg/kg [69.8–225.8 mg/kg]). SXB plasma concentrations were higher post-D2 than post-D1. C8h ranged from 1.91–130 μg/mL. There was no apparent association between D1 Cmax or AUC0-4h, or C8h and gram dose, but a clear association with mg/kg dose. Cmax mean ratio was 1.97 (90% confidence interval [CI]: 1.67–2.31) suggesting dose proportionality, and AUC0-4h mean ratio was 2.53 (90% CI: 2.18–2.94) suggesting supra-dose proportionality. PopPK modelling demonstrated food (extrinsic) and body weight (intrinsic) as the two main factors affecting SXB PK. On a mg/kg basis, SXB is expected to have similar PK across all age groups. Conclusion: SXB PK in children and adolescents exhibited similar properties to those in adults. Plasma concentrations were generally higher post-D2 than post-D1, mainly due to less food effect on D2. Supra-dose proportionality in AUC is consistent with nonlinear clearance of SXB. The clear correlation between exposure and mg/kg, but not gram dose, suggests body weight as an important determinant of SXB PK. Support (If Any): Jazz Pharmaceuticals.